Character Education Based E-Book in Civics Subject for Grade IV Elementary School - Alexsandro, Kris; Simamora, Alexander Hamonangan (Universitas Pendidikan Ganesha, 2023)
The lack of learning media and the use of conventional learning strategies are the main focus of this research. This research aims to analyze the design, validity, and effectiveness of character education-based E-Book in Civics subject for grade IV elementary school. This research uses the ADDIE development model. The data collection methods used in this study were interviews, questionnaires, and observations, and were analysed using quantitative descriptive statistics, and inferential (t-test). The E-Book development design consists of five stages: analysis, design, development, implementation, and evaluation. The results of the validity ranging from content, design, media, individual, and small group test get very good qualifications. Based on the results of the t-test, it is concluded that the character education-based E-Book is effective in learning Civics grade IV at elementary school. The implications of the research have an impact on motivating teachers' insights to create interesting learning media by utilising technology and the ease of students getting learning materials independently anytime and anywhere and applying knowledge and character values obtained from E-Book in daily life.